CMY Color Spaced-Based Visual Cryptography Scheme for Secret Sharing of Data. (9th March 2022) - Sherine, Anli; Peter, Geno; Stonier, Albert Alexander; Praghash, K.; Ganji, Vivekananda
Abstract : Visual cryptography technique allows visual information to be encrypted in such a way that the decrypted information appears as a visual image. Visual cryptography allows digital images to be separate into few shares called transparent shares. For security reasons, it ensures that hackers cannot find any clues about the secret image from a single cover image. The proposed technique uses CMY (cyan, magenta, yellow) color space to enhance visual cryptography, and mean visual cryptography can be used on color images. The other techniques used were color decomposition and error diffusion. Error diffusion is a type of half toning in which the quantization residual is distributed to neighboring pixels that have not yet been processed. The image will be encrypted by four shares which is cyan, magenta, yellow, and mask. Mask will be using random function to random generate half black and half white pixel in 2 × 2 block. Stack all the shares for reviewing the secret image. After that, do the image preprocessing of the image and use OCR (optical character recognition) to recognize the message.